Acquisition and Adaptation of Ultra-small Parasitic Reduced Genome Bacteria to Mammalian Hosts - McLean, Jeffrey S.; Bor, Batbileg; Kerns, Kristopher A.; Liu, Quanhui; To, Thao T.; Solden, Lindsey; Hendrickson, Erik L.; Wrighton, Kelly; Shi, Wenyuan; He, Xuesong (Cell reports (Cambridge), 2020)
The first cultivated representative of the enigmatic phylum Saccharibacteria (formerly TM7) was isolated from humans and revealed an ultra-small cell size (200–300 nm), a reduced genome with limited biosynthetic capabilities, and a unique parasitic lifestyle. TM7x was the only cultivated member of the candidate phyla radiation (CPR), estimated to encompass 26% of the domain Bacteria. Here we report on divergent genomes from major lineages across the Saccharibacteria phylum in humans and mammals, as well as from ancient dental calculus. These lineages are present at high prevalence within hosts. Direct imaging reveals that all groups are ultra-small in size, likely feeding off commensal bacteria. Analyses suggest that multiple acquisition events in the past led to the current wide diversity, with convergent evolution of key functions allowing Saccharibacteria from the environment to adapt to mammals. Ultra-small, parasitic CPR bacteria represent a relatively unexplored paradigm of prokaryotic interactions within mammalian microbiomes. [Display omitted] •Saccharibacteria are ultra-small parasitic bacteria recently discovered in humans•Novel lineages have high genomic diversity within mammalian hosts•Novel lineages are ultra-small, with reduced genomes (<1,000 genes) and a single 16S copy•One group displays minimal genomic changes since transition from environment to humans McLean et al. show that humans are inhabited by a broad diversity of nano-sized bacteria with highly reduced genomes within the Saccharibacteria phylum. They are related to the candidate phyla radiation predominately found in the environment. Saccharibacteria show adaptations and diversification in mammals during their transition from the environment.